Co dzieci myślą o muzyce? Interpretacja muzycznych i literackich treści utworu Sanctus w wypowiedziach dzieci - Ewa Szatan (Problemy Wczesnej Edukacji)
Words are unambiguous and it allows the meaning of phenomena to be defined. Music has many meanings, but words are needed so that music can be described. Children can describe the world in which they live, interpret phenomena. As a researcher I wanted to see how children talk about music as they describe what they hear in it. Text is the result of talking with children about music.